VD_FINDINFO Arrêt / 2024 / 95 vom 4. März 2024 - VD Tribunal cantonal (2024)
DÉFICIENCE MENTALE, AUTISME, ADMISSION DE LA DEMANDE | 8 al. 2 Cst., 42 al. 3 LAI, 3 LPGA, 9 LPGA, 37 al. 3 RAI, 38 al. 1 RAI